In-service Training for Chemistry Teachers’ Proficiency: The Intermediary Effect of Collaboration Based on Teaching Experience - Copriady, Jimmi; Zulnaidi, Hutkemri; Alimin, Masnaini; Rustaman, Rustaman (Eskisehir Osmangazi University, 2018)
This research determined the effect of in-service training, collaboration and teacher proficiency on chemistry subject based on teaching experience. A total of 184 teachers were involved in this study, only 64 of which had less than 10 years of teaching experience. The data were collected via questionnaires and analysed using the software SPSS AMOS 23. The MANOVA test indicated significant differences between in-service training and collaboration based on teachers' teaching experience and parallel results between teacher proficiency in chemistry and teaching experience. The SEM test showed that collaboration has a different intermediary effect on the relationship between in-service training and teacher proficiency. Therefore, chemistry teachers with less teaching experience required additional in-service training and collaboration to enhance their proficiency, whereas experienced chemistry teachers only required in-service training. Results of this study implied that schools should organize collaborative activities that involve teachers with various experiences. Teamwork and collaboration are expected to enhance teacher proficiency in the subject.